Development of a Passive Mini-Direct Ethanol Fuel Cell: Effect of Mea Assembly Parameters by Hot Pressure - Triviño-Bolaños, Diego F.; López-Martínez, Gustavo A.; Camargo-Amado, Rubén J.; Lizcano-Valbuena, William H. (Revista de Ciencias, 2013)
This paper presents preliminary results on the design, construction and evaluation of a passive mini direct ethanol fuel cell (DEFC), capillary fed with 2 mol l-1 aqueous ethanol, at a rate of 2.03 μL min-1, and air oxygen in the cathode through an air vent. Parameters such as pressure, temperature and time of manufacturing a membrane-electrode assembly (MEA) by hot-pressure were evaluated. As the electrode holder used a 0.25 cm2 carbon tissue which was deposited on the catalytic layer (C. L.) for both the anode (0.8 mg cm-2of PtRu/C) and the cathode (0.8 mg cm -2of Pt/C), Nafi on® 115 membranes were used as the electrolyte. The results show, an average power density of 302 μWcm2 under the best conditions used, a catalytic layer with a Nafi on percentage of 50% at 25 °C. A temperature of 125 °C, a pressure of 49.2 Kg/cm2, and 90 seconds duration were used to obtain the MEA.